2019
DOI: 10.1590/s1678-3921.pab2019.v54.01027
|View full text |Cite
|
Sign up to set email alerts
|

Sample size for the estimation of Pearson’s linear correlation in crotalaria species

Abstract: The objective of this work was to determine the necessary sample size to estimate Pearson’s linear correlation coefficients of four species of crotalaria at precision levels. The experiment was carried out with Crotalaria juncea, Crotalaria spectabilis, Crotalaria breviflora, and Crotalaria ochroleuca, during the 2014/2015 crop year. Eight crotalaria traits were evaluated in 1,000 randomly collected pods per species. For each species, the correlation coefficients were estimated for the 28 pairs of traits, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…The two variables might have a strong relationship, but the correlation coefficient could be close to zero [ 13 ]. The relationship between two variables depends on the species, pairing traits, and the magnitude of the correlation coefficient [ 30 ]. Positive associations between the BW and EP traits, and genotype, indicate an increase in BW and EP traits for each increase in the number of dominant alleles (G), while a negative relationship indicates that an increase in the number of dominant alleles (G) is not followed by an increase in AFE and FEW traits.…”
Section: Discussionmentioning
confidence: 99%
“…The two variables might have a strong relationship, but the correlation coefficient could be close to zero [ 13 ]. The relationship between two variables depends on the species, pairing traits, and the magnitude of the correlation coefficient [ 30 ]. Positive associations between the BW and EP traits, and genotype, indicate an increase in BW and EP traits for each increase in the number of dominant alleles (G), while a negative relationship indicates that an increase in the number of dominant alleles (G) is not followed by an increase in AFE and FEW traits.…”
Section: Discussionmentioning
confidence: 99%
“…However, attention should be paid to the significance observed in high magnitude values, due to the small sample of the evaluated data. High magnitude correlation coefficients between traits are needed, when dealing with small samples, according to Sari et al (2017) and Toebe et al (2019). From a practical point of view, although the value of the linear correlation coefficient is not statistically significant, depending on the magnitude, it may have biological significance in the increase or decrease of the means of the traits.…”
Section: Resultsmentioning
confidence: 99%
“…The two variables might have a strong relationship, but the correlation coefficient could be close to zero [13]. The relationship between two variables depends on the species, pairing traits, and the magnitude of the correlation coefficient [30]. Positive associations between the BW and EP traits, and genotype, indicate an increase in BW and EP traits for each increase in the number of dominant alleles (G), while a negative relationship indicates that an increase in the number of dominant alleles (G) is not followed by an increase in AFE and FEW traits.…”
Section: Prl Gene Associations With Reproductive Traitsmentioning
confidence: 99%
“…The FSH gene is reported to affect reproduction and production traits in ILDs [29]. In addition, reproduction and production traits in ducks are also affected by the type or species of livestock [30]. Some studies in Chinese local duck (Shaoxing) have reported that the melatonin receptor genes affect the age of first egg [33].…”
Section: Genotypic Effects Of the Prl Gene On Reproductive Traitsmentioning
confidence: 99%